2016
DOI: 10.7861/clinmedicine.16-2-129
|View full text |Cite
|
Sign up to set email alerts
|

Viral arthritis

Abstract: Acute-onset arthritis is a common clinical problem facing both the general clinician and the rheumatologist. A viral aetiology is though to be responsible for approximately 1% of all cases of acute arthritis with a wide range of causal agents recognised. The epidemiology of acute viral arthritis continues to evolve, with some aetiologies, such as rubella, becoming less common due to vaccination, while some vector-borne viruses have become more widespread. A travel history therefore forms an important part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 51 publications
4
99
0
13
Order By: Relevance
“…Current evidence supports MTX as a potential treatment of viruses mediated arthritis, specifically Parvovirus B19, HBV, HCV, and HIV [185]. Studies documented that pro-inflammatory mediators were markedly decreased after MTX treatment in virus-induced arthritis [186].…”
Section: Methotrexatementioning
confidence: 96%
“…Current evidence supports MTX as a potential treatment of viruses mediated arthritis, specifically Parvovirus B19, HBV, HCV, and HIV [185]. Studies documented that pro-inflammatory mediators were markedly decreased after MTX treatment in virus-induced arthritis [186].…”
Section: Methotrexatementioning
confidence: 96%
“…Furthermore, viruses were recognised among inflammation inducers and factors contributing to OA relapsing nature (Rollín et al, 2007). Previous studies have demonstrated that B19V, hepatitis B and C as well as HIV are among the most common causal agents of virus-mediated arthritis worldwide (Marks et al, 2016). Furthermore, despite the fact that most virus-mediated arthritides are self-limiting, these often require careful consideration of virological, clinical, laboratory and other features to guide physicians in making diagnostic and treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…It is more common in cases of infringement by alphavirus [7] Establishing a definitive diagnosis of viral arthritis is difficult, and often not very useful because no therapeutic impact. It is directly dependent on the demonstration of the infectious agent or at least a specific immune response [10] [11] [13]- [19].…”
Section: Discussionmentioning
confidence: 99%